2022
DOI: 10.3390/nu14142851
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Derivatives in Acute Myeloid Leukemia: The Matter of Selecting the Right Targets

Abstract: Acute myeloid leukemia (AML) is an aggressive and often fatal hematopoietic malignancy. A very attractive way to treat myeloid leukemia, called “differentiation therapy”, was proposed when in vitro studies showed that some compounds are capable of inducing differentiation of AML cell lines. One of the differentiation-inducing agents, all-trans-retinoic acid (ATRA), which can induce granulocytic differentiation in AML cell lines, has been introduced into clinics to treat patients with acute promyelocytic leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…However, the results of small clinical trials with 1,25D against MDS or AML were inconclusive [ 26 ]. Now it seems obvious that 1,25D, or its low calcemic analogs, will not become sole treatment against hematological malignancies, but might be used in combination treatments [ 27 ]. The immuno-stimulating function of 1,25D in hematological malignancies, which are always accompanied by immune dysfunction, is of primary importance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of small clinical trials with 1,25D against MDS or AML were inconclusive [ 26 ]. Now it seems obvious that 1,25D, or its low calcemic analogs, will not become sole treatment against hematological malignancies, but might be used in combination treatments [ 27 ]. The immuno-stimulating function of 1,25D in hematological malignancies, which are always accompanied by immune dysfunction, is of primary importance.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, a study by Lijun Wang et al, [19] further con rmed the correlation between certain allele genes at ve loci, namely HLA-A, HLA-B, HLA-C, HLA-DRB1, and HLA-DQB1, and the occurrence of these diseases. Some of these genes are susceptibility genes, such as [20,21] .Currently, the main methods of treating celiac disease include a gluten-free diet, gliadin peptide enzyme inhibitors, and supplementation of vitamins and minerals. Additionally, an increasing amount of research has revealed the signi cant role that modulating the gut microbiota plays in celiac disease [22,23] .In addition, dysbiosis of the gut microbiota is also an important risk factor for the development of leukemia [24,25] .It is worth mentioning that celiac disease is an immune stress response of the small intestinal epithelium to gluten consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The hormonal form of vitamins D 3 and D 2 , 1α,25-dihydroxyvitamin D 3 /D 2 (1,25D 3/2 ), is a well-known inducer of myeloid differentiation in various nonAPL AML cell types [9,10]. 1,25D 3 is the physiological ligand of the vitamin D receptor (VDR), a member of the nuclear receptor subfamily type II that includes retinoid X receptors (RXRs) and retinoic acid receptors.…”
Section: Introductionmentioning
confidence: 99%